2015
DOI: 10.1128/jb.02429-14
|View full text |Cite
|
Sign up to set email alerts
|

The Flagellar Set Fla2 in Rhodobacter sphaeroides Is Controlled by the CckA Pathway and Is Repressed by Organic Acids and the Expression of Fla1

Abstract: Rhodobacter sphaeroides has two different sets of flagellar genes. Under the growth conditions commonly used in the laboratory, the expression of the fla1 set is constitutive, whereas the fla2 genes are not expressed. Phylogenetic analyses have previously shown that the fla1 genes were acquired by horizontal transfer from a gammaproteobacterium and that the fla2 genes are endogenous genes of this alphaproteobacterium. In this work, we characterized a set of mutants that were selected for swimming using the Fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…All R. sphaeroides cells were grown in Sistrom's minimal medium at 30°C with orbital shaking (18); when indicated, kanamycin (25 g/ml) was added to the culture medium. For the isolation of Fla2 filament-hook basal bodies (HBBs), AM1 cells were grown in Sistrom medium without succinate and in the presence of Casamino Acids (0.2%) with orbital shaking (250 rpm) at 30°C as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…All R. sphaeroides cells were grown in Sistrom's minimal medium at 30°C with orbital shaking (18); when indicated, kanamycin (25 g/ml) was added to the culture medium. For the isolation of Fla2 filament-hook basal bodies (HBBs), AM1 cells were grown in Sistrom medium without succinate and in the presence of Casamino Acids (0.2%) with orbital shaking (250 rpm) at 30°C as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…In R. sphaeroides, the expression of the fla2 genes is dependent on the transcriptional activator CtrA (21). We demonstrated that cheOp1 expression is also dependent on CtrA.…”
Section: Discussionmentioning
confidence: 70%
“…The expression of three chemotaxis proteins encoded in cheOp1 (Fig. 1) was evaluated by Western blotting using total cell extracts obtained from AM1 (25) and its derivative, EA1 (ΔctrA::aadA) (21). The proteins CheY2 and CheY5 were detected in AM1 but not in the absence of ctrA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations